Efecto de la administración de fluidos en la precarga y cocarga e hipotensión arterial en cesáreas electivas en Iquitos 2022 - Calderon Galloza, Jorge Ernesto Aldruval (2025)
GENERAL OBJECTIVE: To evaluate the effect between fluid administration in Preload and Coload and hypotension in elective cesarean sections of the Regional Hospital of Loreto 2022. MATERIALS AND METHODS: A quantitative, cross-sectional and prospective design will be executed. The population will be made up of all pregnant women prioritized for elective cesarean delivery being the sample of 100 pregnant women. CONCLUSIONS: Adequate preventive fluid therapy reduces hypotension and consequent morbidity in women and neonates. Positively impacting the evolution and discharge of the patient who attends elective cesarean section.